Islamic Education During the Covid-19 Pandemic: The Dynamic of Online Learning on Character Education - Mohammad Rindu Fajar Islamy (Nadwa: Jurnal Pendidikan Islam, 2021)
This study explores the Islamic Education learning process dynamics during the Covid-19 Pandemic in the character education activities. The Covid-19 pandemic has changed the learning model from face-to-face to online learning. Developing effective and efficient online learning procedures and forms is a significant challenge faced by teachers. This research study incorporates a qualitative approach where data is collected through observation, interviews, and documentation. The object of the research were three government schools, namely SMPN 3 Lembang, SMKN 10 Bandung, and SMAN 1 Sungailiat Bangka Belitung. The research question is directed to explore the dynamics and problems that arise and the role of teachers and schools in mitigating these problems. The study results showed that most online learning uses popular applications such as Zoom, Google Meet, Google Classroom, Whatsapp Group, and Quizziz. To make online learning effective, among the efforts made by the teacher were explaining the technical activities to be carried out. Constraints that often occurred are limited internet quotas, network constraints, to inadequate computer devices. Amid the challenging situation, learning to shape students' character was still undertaken by internalizing religious values manifested in various forms of simple online religious activities.